(untitled) (American Journal of Arts and Human Science, 2025)
Learners’ engagement is vital for academic success and personal growth in science education, fostering critical thinking and understanding of the natural world. This study examined the engagement levels and science performance skills of Grade 5 pupils in West District Schools, Cagayan de Oro City, for School Year 2024-2025. Engagement was assessed across affective-emotional, cognitive, and behavioral dimensions, while performance skills were evaluated in remembering, understanding, applying, analyzing, evaluating, and creating. Using a descriptive-correlational survey, data were analyzed with descriptive and inferential statistics, including Pearson’s Product Moment Correlation. Findings revealed high emotional engagement but lower cognitive engagement among learners. Performance skills were strongest in evaluating tasks (critical thinking) and weakest in memory-related tasks. A significant positive correlation was identified between cognitive engagement and performance skills, whereas behavioral engagement showed a weaker correlation. The study underscores the importance of emotional and cognitive engagement in science performance. Recommendations include integrating cognitively challenging tasks, employing memory-enhancing techniques, and promoting activities linking behavioral engagement to real-world science applications to improve performance. Teachers are encouraged to create meaningful learning experiences that enhance engagement and foster comprehensive skill development in science.